Proposal for optimization of inspections of electric poles using Lean tools and Last Planner System. An empirical research in Peru (LACCEI, 2024)
The efficiency of the public lighting system in electrical maintenance services is essential and aims to ensure compliance with quality in established times. Currently, the company only achieves 59% of work in a period of 6 months, being the minimum set by the case study of 97% of the total work. This study proposes using Lean tools such as Standardized Work, Line Balance and Last Planner System. For this purpose, the process and the times required for the development of activities in different areas will be standardized. The next step will be to calculate the resources needed to start activities, culminating with planning and continuous improvement. The results were validated in the Arena software, one of the critical indicators being the planning effectiveness index (PEI), which is to be increased by 27% concerning the initial scenario.